Analisis pengaruh sikap finansial, pengalaman finansial dan kepribadian terhadap perilaku manajemen keuangan dimediasi oleh literasi finansial - Amalia, Naili; Hamdani , Muhammad Luthfi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of financial attitudes, financial experience, and financial literacy on financial management behavior. Respondents are Small and Medium Enterprises in the city of Surakarta which found 186 people as a sample. The data were processed using the SPSS version 25 application and the Sobel Online Calculator to test the effect of mediation. The results of this study found that each variable of financial attitude, financial experience and personality had a significant positive effect on the financial literacy of SMEs in the city of Surakarta. Furthermore, in the second equation, the variables of financial attitude, financial experience and personality are known to have a significant positive influence on the financial management behavior of SMEs in Surakarta, but the financial literacy variable does not have a significant effect on financial management behavior. The results of the mediation effect test in this study found that financial literacy could not mediate the indirect effect of financial attitudes, financial experience and personality on the financial management behavior of SMEs in the city of Surakarta.